Circulating long non-coding RNAs NKILA, NEAT1, MALAT1, and MIAT expression and their association in type 2 diabetes mellitus - Irfan Ahmad; Mohammed Alfaifi; Mirza Masroor Ali Beg; Ali Gaithan Alkhathami; Prakash C Joshi; Osama M Alshehri; Abdulrahman Manaa Alamri; Amit Kumar Verma; Mohammad Yahya Alshahrani (BMJ Open Diabetes Research & Care)
Background Type 2 diabetes mellitus (T2DM) is a multifactorial disorder that leads to alterations in gene regulation. Long non-coding RNAs (lncRNAs) have become a major research topic as they are involved in metabolic disorders.Methods This study included a total of 400 study subjects; 200 were subjects with T2DM and 200 were healthy subjects. Extracted RNA was used to synthesize cDNA by quantitative real time. Serum analysis was carried out to determine differences in biochemical parameters. Recorded data were used to evaluate associations with expression of lncRNAs NF-kappaB interacting lncRNA (NKILA), nuclear enriched abundant transcript 1 (NEAT1), metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), and myocardial infarction-associated transcript (MIAT) in T2DM cases.Results Compared with healthy controls, patients with T2DM showed an overall increase in expression of lncRNAs NKILA, NEAT, MALAT1, and MIAT by 3.94-fold, 5.28-fold, 4.46-fold, and 6.35-fold, respectively. Among patients with T2DM, higher expression of lncRNA NKILA was associated with hypertension (p=0.001), smoking (p<0.0001), and alcoholism (p<0.0001). Altered NEAT1 expression was significantly associated with weight loss (p=0.04), fatigue (p=0.01), slow wound healing (p=0.002), blurred vision (p=0.008), loss of appetite (p=0.007), smoking (p<0.0001), and alcoholism (p<0.0001). Higher expression of lncRNA MALAT1 was significantly linked with weight loss (p=0.003), blurred vision (p=0.01), smoking (p<0.0001), and alcoholism (p<0.0001). Expression of lncRNA MIAT was associated with only blurred vision (p<0.0001), smoking (p<0.0001), and alcoholism (p<0.0001). Positive correlations of lncRNA NKILA with lncRNAs NEAT1 (r=0.42, p<0.0001), MALAT (r=0.36, p<0.0001) and MIAT (r=0.42, p<0.0001) were observed among patients with T2DM. Significant positive correlations of lncRNA NEAT with lncRNAs MALAT and MIAT were observed among patients with T2DM. A positive correlation between lncRNAs MALAT and MIAT was also observed among patients with T2DM.Conclusion Increased circulating NKILA, NEAT1, MALAT, and MIAT expression in patients with T2DM, which is linked with poor patient outcomes and significantly linked with alcoholism and smoking, may influence the degree and severity of disease among patients with T2DM. These lncRNAs may contribute to the progression of T2DM disease or other related diabetes-related complications.